Exploratory study of the change occurred in five ecophysiological variables of corn (stages V8-R1) in Serdán, Puebla - Contreras-Ramos, Juan; Díaz-Ruíz, Ramón; Pérez-Ramírez, Efraín (Revista Mexicana de Ciencias Agrícolas, 2023)
For Mexico, precipitation and maximum and minimum temperatures are climatic variables of interest since most of its agricultural area is under rainfed conditions, a situation that makes the country vulnerable to climate change. The study of climate change is carried out at different scales, with those carried out in regional weather stations currently standing out. The present study was conducted in the Serdán Valley, in the state of Puebla, where the great agrodiversity of crops (28) that existed in the 40s has decreased at present to only six, for climatic and economic reasons, having little diversity of varieties, the producer depends mainly on corn, the most adapted to the current climatic changes that occur in the valley. The general objective was: to evaluate the local changes in temperature and precipitation in two different research periods and their current influence on five ecophysiological variables of the corn crop in the 60 days of greatest growth dynamics. The bibliographic review and statistical analysis of the climatic changes that occurred in the local weather stations and their influence on the ecophysiological variables selected for the study allowed us to conclude that the research carried out in the two research periods (1975-1981, 2010-2018) was conducted under different climatic conditions of rainfall and temperatures, but that the current adaptation of landrace corn and cultivation practices have resulted in better yields.